Determinants of training and the impact of training on company performance level: evidence from MSC Malaysia status companies - Zulkifli, Izyani; Duasa, Jarita (2009)
The study attempts to provide a brief discussion on human capital development in Malaysia. Using data from online survey of companies in MSC Malaysia, it (1) compares the quantity and quality of training between local and foreign MSC Malaysia status companies, (2) analyzes the factors that affect the occurence and magnitude of training for these companies as whole, and (3) examines the impact of training on company performnace level. The findings indicate that there is no difference in the quantity of training provided between local and foreign MSC Malaysia status companies, although the latter provides significantly better quality training than their local counterparts. Training is more likely to occur among larger MSC Malaysia status companies, those with lower worker turnover rates, those with more full-time knowledge workers and those with a formal training policy. The magnitude of training provided, however, is largely determined by the size of the company, a strong internal labour market, greater share of R&D expenditures and the undertaking of training grants. Result also show that the total number of knowledge workers trained does have a positive and significant effect on company performance level.